Green synthesis of carbon quantum dots from Euglena gracilis for antibacterial and bioimaging applications - Cheng, Hao; Yang, Chenglong; Xu, Weicheng; Deng, Ziai; Guan, Ge; Zahid, Hussain; Liu, Yi; Hu, Beibei; Qin, Zhanke; Ren, Maozhi (Frontiers in Nanotechnology, 2025)
IntroductionCarbon quantum dots (CQDs) are a promising class of zero-dimensional carbon nanomaterials (<10 nm) that can be synthesized from organic precursors. They have attracted intense attentions due to their high water solubility, nontoxicity, excellent biocompatibility, and strong optical properties. Microalgae offer a low-cost, renewable, and eco-friendly source of carbon for CQD synthesis. Their high carbon content, functionalization potential, and biocompatibility make them ideal precursors for producing CQDs with excellent properties and versatile applications.MethodsIn this study, we explored the synthesis of Euglena gracilis-derived CQDs (E-CQDs) via a one-step hydrothermal green synthesis method and investigated their potential application in bioimaging and antibacterial materials. The synthesized E-CQDs were comprehensively characterized using TEM, XRD, FTIR, XPS, and UV-vis analysis.ResultsThe TEM images showed that E-CQDs had a spherical shape with diameters ranging from 6.5 to 10.5 nm. The XRD patterns indicated that the E-CQDs were crystalline in nature. The FTIR results suggested that E-CQDs were functionalized with C-N and N-H bonds. XPS analysis showed that the E-CQDs were mainly composed of carbon,nitrogen, oxygen and silicon. The UV-vis spectra exhibited a peak at a wavelength of 252 nm, indicating strong absorption in the ultraviolet region. The antibacterial activity test demonstrated that E-CQDs had high inhibitory activity against Escherichia coli and Staphylococcus aureus, causing damage to their cell membranes. Additionally, the bioimaging assay indicated E-CQDs possessed the capacity for bioimaging applications in cells, such as Chlorella.DiscussionThis work presents a green synthesis approach for microalgae-derived CQDs, overcoming some environmental drawbacks of traditional chemical methods. It validates the dual-function paradigm where a single nanomaterial can simultaneously suppress bacterial growth and enable bioimaging.